Trend of economic structure transfering in Vietnam - Nguyễn Thị Tuyết Mai (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
A country that wants to develop and achieve high economic growth rates must have a reasonable industry structure. In recent years, the restructuring of Vietnam's economic sector has been oriented towards industrialization and modernization, which helps to promote the comparative advantages of industries and territories. As a result, after more than 30 years of Doi moi reform, Vietnam's economy has achieved many important achievements and potentials. In order to obtain the goal of industrialization and modernization, Vietnam’s economy is necessary to be restructured in the direction of improving productivity, quality and efficiency in association with promoting international economic integration.